2022
DOI: 10.1108/jsm-09-2020-0407
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumer perceptions and attitudes toward smart retail services

Abstract: Purpose This study aims to identify the antecedent factors influencing consumer attitudes and patronage intentions toward an intelligent unmanned convenience store (IUCVS) in Taiwan. The IUCVS is a new smart service that offers customers a novel shopping experience, given that it avoids queues and physical contacts with cashiers. However, studies discussing IUCVS remain scant owing to its brief history. Design/methodology/approach This research develops a synergistic model combining original unified theory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 66 publications
2
27
0
2
Order By: Relevance
“…The seventh hypothesis (H7) of the study is whether attitude has a positive influence on BI to use SHTs. The study found a significant positive impact of attitude on BI to use SHTs, consistent with past studies [69,70]. This present study confirms the importance of attitude in predicting BI to use SHTs among elderly people in Saudi Arabia because when the elderly have a positive attitude towards SHTs, they are more expected to increase their intention to use SHTs.…”
Section: Findings Of the Direct Hypothesessupporting
confidence: 91%
See 2 more Smart Citations
“…The seventh hypothesis (H7) of the study is whether attitude has a positive influence on BI to use SHTs. The study found a significant positive impact of attitude on BI to use SHTs, consistent with past studies [69,70]. This present study confirms the importance of attitude in predicting BI to use SHTs among elderly people in Saudi Arabia because when the elderly have a positive attitude towards SHTs, they are more expected to increase their intention to use SHTs.…”
Section: Findings Of the Direct Hypothesessupporting
confidence: 91%
“…This suggests that individuals with an overall positive attitude toward behavioural intention to use SHTs are more likely to accept SHTs than those with a negative attitude toward the technologies. Some studies have found that the explanatory power of BI increases when the attitude is included in the UTAUT model [ 69 , 70 ]. This present study aims to investigate the effect of attitude and BI to use SHTs among elderly people in Saudi Arabia.…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Li and Fang, 2019, p. 1), "information system initial adoption is different from the postadoption behaviour", such as continuance intention, and previous studies mainly examined the initial adoption of Apps relying on the theory of planned behaviour (Cheung andTo, 2017, Wu andSong, 2021), value-based adoption model (Erdmann et al, 2021), technology acceptance model (Oyman et al, 2022), and unified theory of acceptance and use of technology (Lin, 2022). The aforementioned studies were not studied on retail Apps service delivery and the literature lacks a solid model on the continuance intention of retail Apps services.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
“…Akıllı perakendecilik alanındaki araştırmaların daha çok tüketici davranışları üzerine yoğunlaştığı görülmektedir (Pantano ve Migliorese, 2014;Paydar, Endut, Yahya, ve Rahman, 2014;Pantano ve Priporas, 2016;Kim vd., 2017;Vazquez, Dennis, ve Zhang, 2017;Priporas, Stylos, ve Fotiadis, 2017;Roy, Balaji, Quazi, ve Quaddus, 2018;Bourg, Chatzidimitris, Chatzigiannakis, Galavas, Giannakopoulou, Kasapakiz, Konstantopoulos, Kypriadis, Pantziou, ve Zaroliagis, 2020;Chang ve Chen, 2021;Chen ve Shang, 2021;Lin, 2021). Ancak bildiğimiz kadarıyla mevcut araştırmaların çoğu akıllı teknolojilerle müşteri deneyiminden ziyade akıllı teknolojilerin benimsenmesini ve kabul edilmesini ele almıştır (Pantano ve Servidio, 2012;Rese, Schreiber, ve Baier, 2014;Priporas vd., 2017;Roy vd., 2018;Foroudi, Gupta, Sivarajah, ve Broderick, 2018;Roy, Singh, ve Shabnam, 2021).…”
Section: Literatür Taramasıunclassified